Longitudinal Associations among Machiavellianism, Popularity Goals, and Adolescents' Cyberbullying Involvement: The Role of Gender - Wright, Michelle F.; Wachs, Sebastian; Huang, Zheng; Kamble, Shanmukh V.; Soudi, Shruti; Bayraktar, Fatih; Shu, Chang (Routledge Journals, Taylor & Francis Ltd, 2022)
Drawing on the social-ecological perspective, this longitudinal study investigated the potential moderating effect of gender in the relationships among Machiavellianism, popularity goals, and cyberbullying involvement (i.e. victimization, perpetration) among adolescents from China, Cyprus, India, and the United States. There were 2,452 adolescents (M-age = 14.85; SD = .53; 13-16 years old; 49.1% girls) from China, Cyprus, India, and the United States included in this study. They completed surveys on Machiavellianism, popularity goals, and cyberbullying victimization and perpetration during the fall of 2014 (Time 1). One year later, during the fall of 2015, adolescents completed surveys on cyberbullying victimization and perpetration. Findings revealed that Machiavellianism and popularity goals were both associated positively with Time 2 cyberbullying victimization and perpetration for all adolescents. The associations between Machiavellianism and Time 2 cyberbullying perpetration and between popularity goals and Time 2 cyberbullying perpetration were stronger for Chinese and Indian boys than girls. Opposite patterns were found for popularity goals and Time 2 cyberbullying perpetration for adolescents from the United States. Gender did not moderate any of the associations for Cypriot adolescents or for Time 2 cyberbullying victimization. The social-ecological perspective provides a useful understanding of how various contexts influence bullying.
Keywords: Machiavellianism; popularity goal; cyberbullying; culture; gender